2020
DOI: 10.1111/liv.14625
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of multiparametric magnetic resonance imaging, transient elastography and blood‐based fibrosis markers in patients with chronic liver disease

Abstract: Prognostic value of multiparametric magnetic resonance imaging, transient elastography and blood-based fibrosis markers in patients with chronic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 45 publications
0
61
0
Order By: Relevance
“…When stratifying cT1 into groups (<840 , 840-990 , >990 ms), the risk of clinical events is increasing with increasing cT1. [36] Similarly, in a biopsy-confirmed mouse model of advanced NASH, hepatic pathology improved and NAFLD activity and expression of collagen genes (Col1a1 and Col4a1) were reduced upon Mastiha intake. [19] In our study, we showed that the Bray-Curtis dissimilarity index was significantly greater among patients with NAFLD that received the Mastiha, compared to the Placebo.…”
Section: Discussionmentioning
confidence: 99%
“…When stratifying cT1 into groups (<840 , 840-990 , >990 ms), the risk of clinical events is increasing with increasing cT1. [36] Similarly, in a biopsy-confirmed mouse model of advanced NASH, hepatic pathology improved and NAFLD activity and expression of collagen genes (Col1a1 and Col4a1) were reduced upon Mastiha intake. [19] In our study, we showed that the Bray-Curtis dissimilarity index was significantly greater among patients with NAFLD that received the Mastiha, compared to the Placebo.…”
Section: Discussionmentioning
confidence: 99%
“…MRI scanning was performed using Liver MultiScan image acquisition protocols [24][25][26]. For LMS-IDEAL PDFF measurements, four sets of transverse images of the liver were acquired at the level of the portal vein.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…These developments have resulted in a technique, referred to here as LMS-IDEAL, that quantifies liver fat in a standardised way across different manufacturers and field strengths. LMS-IDEAL is integrated in the multiparametric MRI technology, Liver MultiScan 1 (Perspectum, UK), a diagnostic aid to quantitatively characterise liver tissue in terms of fat, iron, fibrosis and inflammation [24][25][26]. Liver MultiScan's standardised measurements allow data from larger cohorts, comprising participants from different studies, locations and scanners to be combined in a single analysis.…”
Section: Introductionmentioning
confidence: 99%
“…12 patients presented with a diagnosed underlying liver disease. MpMRI was performed in all patients and 21% of individuals (29/135) had pre-operative liver cT1 values greater than the upper limit of normal (795 ms) defined for the general population [34,35].…”
Section: Resultsmentioning
confidence: 99%
“…In the subset of patients where at least 10% of the liver volume was removed (n = 77), the median length of stay for patients with pre-operative cT1 above the upper limit of normal (�795ms) was 1.5 days longer than those presenting with cT1 within the normal range (Fig 4). Other variables (presence of comorbidities, resection volume greater than 50%, preoperative bilirubin level above normal (20 μmol/L), total lesion volume above 100ml, age over 60 years, Bilirubin (μmol/L) 10 [8][9][10][11][12][13][14][15][16][17][18][19] Albumin (μmol/L) 39 [36][37][38][39][40] AST (U/L) 26 [22][23][24][25][26][27][28][29][30][31][32] ALT (U/L) 23 [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] ALP…”
Section: Pre-operative Multiparametric Mri Correlates With Length Of mentioning
confidence: 99%